Site-Specific Interaction between α-Synuclein and Membranes Probed by NMR-Observed Methionine Oxidation Rates - Maltsev, Alexander S. (American Chemical Society, 2013)
[Image: see text] α-Synuclein (αS) is an intrinsically disordered protein that is water-soluble but also can bind negatively charged lipid membranes while adopting an α-helical conformation. Membrane affinity is increased by post-translational N-terminal acetylation, a common modification in all eukaryotic cells. In the presence of lipid vesicles containing a small fraction of peroxidized lipids, the N-terminal Met residues in αS (Met1 and Met5) rapidly oxidize while reducing the toxic lipid hydroperoxide to a nonreactive lipid hydroxide, whereas C-terminal Met residues remain unaffected. Met oxidation can be probed conveniently and quantitatively by NMR spectroscopy. The results show that oxidation of Met1 reduces the rate of oxidation of Met5 and vice versa as a result of decreased membrane affinity of the partially oxidized protein. The effect of Met oxidation on the αS–membrane affinity extends over large distances, as in the V49M mutant, oxidation of Met1 and Met5 strongly impacts the oxidation rate of Met49 and vice versa. When not bound to membrane, oxidized Met1 and Met5 of αS are excellent substrates for methionine sulfoxide reductase (Msr), thereby providing an efficient vehicle for water-soluble Msr enzymes to protect the membrane against oxidative damage.